2012
DOI: 10.1073/pnas.1114297109
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell movement of plastids in plants

Abstract: Our objective was to test whether or not plastids and mitochondria, the two DNA-containing organelles, move between cells in plants.As our experimental approach, we grafted two different species of tobacco, Nicotiana tabacum and Nicotiana sylvestris. Grafting triggers formation of new cell-to-cell contacts, creating an opportunity to detect cell-to-cell organelle movement between the genetically distinct plants. We initiated tissue culture from sliced graft junctions and selected for clonal lines in which gent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…Thus, far when cell-to-cell movement of plastids was observed, the entire selected plastid genome was recovered, rather than a ptDNA fragment comprising the selected marker. Absence of recombination between the plastid genomes suggested movement of intact organelles rather than naked, fragmented DNA (11,12). Indeed, chloroplasts rarely fuse (22), precluding recombination that enables new combinations of chloroplast genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, far when cell-to-cell movement of plastids was observed, the entire selected plastid genome was recovered, rather than a ptDNA fragment comprising the selected marker. Absence of recombination between the plastid genomes suggested movement of intact organelles rather than naked, fragmented DNA (11,12). Indeed, chloroplasts rarely fuse (22), precluding recombination that enables new combinations of chloroplast genes.…”
Section: Discussionmentioning
confidence: 99%
“…The flower phenotype of plants carrying orf293 in mitochondria depends on the nuclear background: in N. tabacum the anthers are petaloid, or petaloidstigmatoid (Fig. 1D); in N. sylvestris, the anthers are converted into stigmatoid structures (11). Based on the flower phenotype, we tentatively named orf293 "homeotic conversion of anthers" (hca) gene.…”
Section: Expression Of Orf293 Correlates With Homeotic Conversion Of mentioning
confidence: 99%
See 2 more Smart Citations
“…The cytomictic migration of plastids attracts a special attention, since it has been repeatedly demonstrated that the plastids carrying selective traits can migrate between cells of vegetative tissues at the zone of transplant fusion (Stegemann and Bock 2009;Thyssen et al 2012). Presumably, CCs also play a key role in this case; however, the mechanisms of their formation in somatic tissues require a separate study.…”
Section: Cytological Picture Of Cytomixismentioning
confidence: 99%